Internet censorship detected in Venezuela (Venezuela) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Venezuela. Data sourced from CensoredPlanet.
Censorship Incident ID: VE-2026-0403. Severity: critical. Confidence: 65%